(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
In the first half of the 90s, computers of adequate speed of operation and processing softwares became increasingly available, made it possible to realize 3D surface characterisation. In the literature different directives can be found none of them has become widely used. Beside the extension of 2D parameter based technique to 3D many other methods have been developed. One is the power spectral density (PSD) technique when “global” surface characterisation is carried out using complex mathematical tools. Nowadays one of the most important tasks in tribology to design the surfaces optimised to the operation. In the present study topographical measurements and PSD characterizations were performed to study the engineering surfaces produced by turning and to analyse the effectiveness of 2D and 3D PSD.